The Crowded Desert: Let's Explore Archaeology Presentation - Shaima Sherif (16020527) (2023)
This item is a Illustrated Presentation produced by UCL Qatar as part of the The Crowded Desert Project, and is part of Crowded Desert School Pack - English collection.  The Illustrated Presentation  is for 6 - 11 years age groups. This work was illustrated by Marsya Abdulghani.